Contrasting the crystallinity indicators of heated and diagenetically altered bone mineral - Rogers, Keith; Beckett, Sophie; Kuhn, Samira; Chamberlain, Andrew; Clement, John (Elsevier, 2010)
Modifications to bone mineral as a result of diagenesis or heating include a marked increase in crystallinity. Although these processes are not completely understood a number of simple, pragmatic approaches are in general use to quantify crystallinity and thus provide a relative metric for features such as preservation state. A preliminary investigation into the interpretation of crystallinity as measured by X-ray diffraction has been undertaken. The microstructural changes associated with diagenetically altered (archaeological) and heated contemporary bone have been examined. A common analysis approach was adopted and thus direct comparison between the physical features of these material systems has been possible. The data clearly demonstrate the pronounced anisotropic nature of the crystallite microstructure for both diagenetically altered and contemporary bone. The limitations of adopting simple crystallinity indices for characterising such materials are explored. Crystallite size and strain were shown to be dependent upon crystallographic direction. Overall, the diagenetically altered bone mineral possessed greater long range lattice order than that of contemporary heated bone. Further, significant differences between the directional nature of the microstructure of diagenetically altered and modern heated bone were observed. This study has enabled a direct comparison of the effects of heating and diagenesis upon bone mineral. It has demonstrated the need to consider bone microstructure anisotropically.
Keywords: Bone; Crystallinity; X-ray diffraction; Diagenesis